A cm scale electret-based electrostatic wind turbine for low-speed energy harvesting applications. (14th March 2016) - Perez, M; Boisseau, S; Gasnier, P; Willemin, J; Geisler, M; Reboud, J L
Abstract: This paper presents a small-scale airflow energy harvester built on an axial turbine architecture and exploiting an electret-based electrostatic converter. When the airflow velocity is high enough, the windmill starts rotating and creates a periodic relative motion between a stator and a rotor which induces variations of capacitance. These ones are directly converted into electricity thanks to the use of Teflon electrets charged at −1400 V which polarize the variable capacitors. We focus our study on a 4-blade axial turbine with a diameter of D  = 40 mm, a depth of W  = 10 mm, for a total volume of 12.6 cm 3 . This windmill has been tested with various blade angles and different types of electrostatic converters and output powers up to 90 μ W at 1.5 m s −1 (7.5 μ W cm −3 ) and 1.8 mW at 10 m s −1 (111 μ W cm −3 ) have been obtained so far. The coefficient of power reaches C p  = 5.8% and among the small-scale airflow energy harvesters previously reported, this one has the lowest cut-in speed (1.5 m s −1 ).